Choice of criterias for setting correspondence between terms in bases of knowledge - Ляшкевич, Василь Яремович; Олар, Оксана Яремовна (Eastern-European Journal of Enterprise Technologies, 2014)
In constructing bases or warehouses of knowledge, ontology of the arbitrary thematic branch, the issue of choosing the method of setting correspondence between terms (concepts) is always topical. Among the many approaches to setting the correspondence between the terms in bases or warehouses of the knowledge domain "Intelligence diagnostics of computer means" the most common is the use of tables with diagnostic information such as "object - property", which can be described by Cartesian product. But using a binary relation, we can answer the question: "Is there the relation?" Today it would be expedient to get the answer to the question: "Which of diagnostic means are more effective?" The answer to this question can be obtained from the diagnostics results. The normalized value of diagnostics software efficiency can be used for setting correspondence between terms (concepts) such as "Object - Property" for example, in the table of knowledge "Models of computer means - Diagnostics means" and others.